Oceana or England and he colonies - Froude, James Anthony (London : Longmans, Green and Co, 1888)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: reisverslagen; kolonialisme; Verenigd Koninkrijk; Oceanië